The genetics of NOD-like receptors in Crohn's disease. - Cummings, JR; Cooney, R; Clarke, G; Beckly, J; Geremia, A; Pathan, S; Hancock, L; Guo, C; Cardon, L; Jewell, D (2010)
The first Crohn's disease (CD) susceptibility gene identified was CARD15, which is a member of the emerging NOD-like receptor (NLR) family. These function as intracellular cystosolic pattern recognition receptors (PRRs) and play a central role in the innate immune response. We studied other members of the NLR family using a gene-wide haplotype tagging approach in a well-characterised collection of 547 CD patients and 465 controls. Four single nucleotide polymorphisms (SNPs) in NLRP3 had P values < 0.05 and are in high linkage disequilibrium (LD) with each other (r(2) > 0.90 for all four SNPs). rs4925648 and rs10925019 were the most strongly associated with CD susceptibility (P = 0.001, odds ratio (OR) 1.62, 95% CI 1.2-2.18; and P = 6.5 x 10(-4), OR 1.65, 95% CI 1.23-2.19, respectively). rs1363758 located in NLRP11 was associated with CD susceptibility [P = 0.002 (1.64, 1.19-2.25)], which was weakly confirmed in an independent case-cohort collection on joint analysis [P = 0.05, (1.28, 1-1.64)]. On sub-phenotype analysis, an interesting association between NLRP1 and skin extra-intestinal manifestations and colonic, inflammatory CD was identified. None of these results was replicated in the Wellcome Trust Case Control Consortium study and therefore need replication in a further large cohort.